Awareness of Medan Area Students in Demanding Against the Law of Drug Abuse, the Prevention of Radicalism and Terrorism - Zaini Munawir S; Abdul Lawali Hasibuan (Budapest International Research and Critics University, 2020)
The progress of a nation can be seen from the level of legal awareness of its citizens. The higher the legal awareness of a country's population, the more orderly life of society and the state. Conversely, if the legal awareness of a country's population is low, what applies there is jungle law. Does the legal awareness of today's society need to be increased? Has it declined so much? What can we overcome in today's society related to legal awareness? In accordance with what has been stated above, that legal awareness is essentially awareness of the existence or occurrence of